2020
DOI: 10.1111/dmcn.14635
|View full text |Cite
|
Sign up to set email alerts
|

Communication disorders in young children with cerebral palsy

Abstract: Aim To test the prediction of communication disorder severity at 5 years of age from characteristics at 2 years for children with cerebral palsy (CP) whose communication is giving cause for concern. Method In this cohort study, 77 children (52 males; 25 females) with communication difficulties and CP were visited at home at 2 (mean 2y 4mo; SD 3mo) and 5 (mean 5y 5mo; SD 4mo) years of age. Information on the type and distribution of motor disorder, seizures, gross and fine motor function, hearing, and vision we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 33 publications
5
21
0
Order By: Relevance
“…12 In a cohort of children with CP aged 2 to 8 years, primarily with a spastic presentation, Hustad and colleagues found that no speech development at 2 years was a risk factor for significant communication difficulties at 4 years of age. 8,13 Similar patterns in communication development have been reported by Pennington et al, 14 where children with a bilateral spastic or dyskinetic CP presentation and limited speech at 2 years were at the highest risk of speech and communication impairment at 5 years. To address this, communication assessment and multimodal communication intervention has been advocated, 12,14 with increasing emphasis on augmentative and alternative communication (AAC) to optimize academic participation for older children.…”
supporting
confidence: 77%
See 4 more Smart Citations
“…12 In a cohort of children with CP aged 2 to 8 years, primarily with a spastic presentation, Hustad and colleagues found that no speech development at 2 years was a risk factor for significant communication difficulties at 4 years of age. 8,13 Similar patterns in communication development have been reported by Pennington et al, 14 where children with a bilateral spastic or dyskinetic CP presentation and limited speech at 2 years were at the highest risk of speech and communication impairment at 5 years. To address this, communication assessment and multimodal communication intervention has been advocated, 12,14 with increasing emphasis on augmentative and alternative communication (AAC) to optimize academic participation for older children.…”
supporting
confidence: 77%
“…Children in this study with poor manual ability (Mini‐MACS levels III–V, n =7) were classified with less effective communication skills (FCCS levels IV and V) than children with more independent manual ability. In another study, Pennington et al 14 found that MACS ratings at 2 years predict FCCS classification at 5 years, especially for MACS levels III and IV.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations